Extracellular Vesicles: Emerging Players in Plant Defense Against Pathogens - Liu, Guosheng; Kang, Guangren; Wang, Shumei; Huang, Yifan; Cai, Qiang (Frontiers in Plant Science, 2021)
Communication between plants and interacting microorganisms requires functional molecule trafficking, which is essential for host defense and pathogen virulence. Extracellular vesicles (EVs) are single membrane-bound spheres that carry complex cargos, including lipids, proteins, and nucleic acids. They mediate cell-to-cell communication via the transfer of molecules between cells. Plant EVs have been isolated from many plant species and play a prominent role in immune system modulation and plant defense response. Recent studies have shown that plant EVs are emerging players in cross-kingdom regulation and contribute to plant immunity by mediating the trafficking of regulatory small RNA into pathogens, leading to the silencing of pathogen virulence-related genes. This review summarizes the current understanding of plant EV isolation technologies, the role of plant EVs in plant immunity, and the mechanism of plant EV biogenesis, as well as approaches for how these findings can be developed into innovative strategies for crop protection.